Prostate-Specific Antigen and Time to PSA Nadir as Prognostic Significance in Castration-Resistant Prostate Cancer - Pranata, Firmantya Hadi; Djatisoesanto, Wahjoe; Soebadi, Doddy M. (Folia Medica Indonesiana, 2022)
Highlight: • Assessing the survival rate in castration-resistant prostate cancer was descriptived. • PSA level between survivor and non survivor was significant but not for PSA nadir level, TTN and TTC. • Initial PSA level can predict survival prognosis rate of castration-resistant prostate cancer patients. Abstract: High mortality rates was often found in castration-resistant prostate cancer (CRPC). Our aim on this research was to assess the PSA level and time to PSA nadir as a prognostic tool for survival in CRPC patients. Several factors are considered to be useful as prognostic marker in CRPC patients. This study was a descriptive study assessing the survival rate in castration-resistant prostate cancer. Evaluation data included sex, age, initial PSA level, final PSA level, time to PSA nadir (TTN), time to CRPC progression (TTC), and survival status. A total of 24 patients with CRPC were evaluated in this study. There was significant difference found of initial PSA level between survivor (445.7 + 165.6 ng/mL) and non-survivor (200.7 + 144.9 ng/mL). There were no significant differences were also found in PSA nadir level, TTN and TTC between survivor and non-survivor groups. This study revealed that there was association between initial PSA level on survival rate of CRPC patients. Initial PSA level could be used to predict survival prognosis in CRPC patients.